Derivatives market development and pricing on derivatives in Ukraine - Matseliukh, Nataliia Petrivna; Мацелюх, Наталія Петрівна (Незалежний АУДИТОР, 2016)
The aim of this paper is to define the specifics of derivatives pricing, taking into account the features of the development of the derivatives market in Ukraine. The emergence of innovative derivative financial instruments is caused the need of new approaches to pricing on them. Prices for innovative derivative financial instruments may depend on several bases. This situation exacerbates the risk of asymmetric information in the securities market. Innovative derivatives pricing processes depends on the dynamics of the market of securities, including derivatives market. Global derivatives market is growing faster than the market benchmark asset that increases the likelihood of price imbalances. The emergence of structured financial products has increased the risk of virtual value because one underlying asset can be used for a number of complex derivatives. This situation requires a legislative settlement treatment of derivatives and the formation of prices in Ukraine. Special legislation should define the rules for derivatives treatment and pricing. Such rules should aim at reducing the facts release derivatives one basis and full disclosure to all market participants.

Метою статті є виявлення специфіки ціноутворення на деривативи з урахуванням особливостей розвитку похідних цінних паперів в Україні. Поява інноваційних похідних фінансових інструментів зумовлює необхідність перегляду підходів до ціноутворення на них. Ціни на інноваційні похідні фінансові інструменти можуть залежати від кількох базисів. Така ситуація вносить додатковий ризик поглиблення асиметрії інформації на ринку цінних паперів. Процеси ціноутворення на інноваційні деривативи залежать від динаміки розвитку ринку цінних паперів, у тому числі строкового ринку. Світовій ринок деривативів зростає швидшими темпами, ніж ринок базисних активів, що збільшує ймовірність цінових дисбалансів. Поява структурованих фінансових продуктів зумовила зростання ризику виникнення віртуальної вартості, оскільки на один базисний актив може бути випущено кілька складних деривативів. Така ситуація вимагає законодавчого врегулювання обігу деривативів та формування цін на них в Україні. Спеціальне законодавство про деривативи має визначати правила їх обігу та процедуру ціноутворення. Такі правила мають бути направлені на зменшення фактів випуску деривативів на один базис та повне розкриття такої інформації для всіх учасників ринку.
Розвиток ринку деривативів та ціноутворення на них в Україні
Keywords: деривативи; ціноутворення; структурований фінансовий продукт; ф’ючерс; опціон; індекс; derivatives pricing; structured financial product futures; index option